1985
DOI: 10.1111/j.1365-2125.1985.tb02654.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated doses of enalapril on renal function in man.

Abstract: Ten healthy subjects received 10 mg oral enalapril (MK 421) daily for a period of 8 days. Renal clearances of electrolytes, urate and phosphate were monitored and factored for glomerular filtration rate, as measured by creatinine clearance, with particular emphasis on the first and eighth day of treatment. Apart from a fall of around 10% in creatinine clearance between 1‐2 h on both days 1 and 8, GFR remained unchanged throughout the study. Fractional sodium excretion increased in a biphasic manner by approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

1986
1986
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
2
5
1
Order By: Relevance
“…Reports on a chronic natriuretic effect of enalapril are less consistent: McNabb et al [23] reported a volume depletion still to be present after 1 week of treatment, but others saw no effect [22,24]. In the present study, we found neither an acute natriuresis nor any evidence for sodium depletion after 2 weeks.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Reports on a chronic natriuretic effect of enalapril are less consistent: McNabb et al [23] reported a volume depletion still to be present after 1 week of treatment, but others saw no effect [22,24]. In the present study, we found neither an acute natriuresis nor any evidence for sodium depletion after 2 weeks.…”
Section: Discussioncontrasting
confidence: 48%
“…Angiotensin-converting enzyme (ACE) inhibitors as enalapril exert some natriuretic effect in acute studies in man [20][21][22][23]. Reports on a chronic natriuretic effect of enalapril are less consistent: McNabb et al [23] reported a volume depletion still to be present after 1 week of treatment, but others saw no effect [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Natriuresis occurs with captopril and enalapril in normotensive and hypertensive subjects on both normal and low sodium intakes (MacGregor et al, 1980;de Zeeuw et al, 1983;Lant et al, 1984). A concomitant rise in urinary phosphate and urate excretion (de Zeeuw et al, 1983;Leary et al, 1985;McNabb et al, 1985) suggests that ACE inhibition may also be directly inhibiting proximal tubular transport of these ions.…”
Section: Intrarenal Effectsmentioning
confidence: 99%
“…A concomitant rise in urinary phosphate and urate excretion (de Zeeuw et al, 1983;Leary et al, 1985;McNabb et al, 1985) suggests that ACE inhibition may also be directly inhibiting proximal tubular transport of these ions.…”
Section: Intrarenal Effectsmentioning
confidence: 99%
“…The effect on the glomerular filtration rate is variable and depends on the experimental conditions (Mimran et al, 1979;Hollenberg et al, 1981;McNabb et al, 1986;Navis et al, 1986). Captopril and enalapril cause acute natriuresis (Brunner et al, 1981;Hollenberg et al, 1981;McNabb et al, 1986;Navis et al, 1986) which may be accompanied by potassium retention (Atlas et al, 1979;Navis et al, 1986) or in the case of enalapril by kaliuresis (McNabb et al, 1985(McNabb et al, , 1986. Both drugs have been reported to increase prostaglandin levels (Swartz et al, 1980;Oparil et al, 1983) but there are no data for cilazapril.…”
Section: Introductionmentioning
confidence: 99%